Empowering Inclusion of Children with Disabilities: Administrative and Leadership Requirements in Kindergarten Stage - Alhammadi, Muteb; Alsuhaymi, Abdulaziz; Eltantawy, Mahmoud Mohamed (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Inclusion of children with disabilities in the kindergarten stage is crucial not only from humanitarian and legal standpoints but also from the standpoint of creating an inclusive society of harmonious coexistence with those with disabilities in the work environment and in social and familial contexts. Objective: This study aimed to determine the degree of availability of administrative and leadership requirements for including children with disabilities in the kindergarten stage, considering the viewpoints of special education teachers and kindergarten teachers and the differences in their responses based on their specialization and years of experience. Methods: A self-administered questionnaire survey on 103 kindergarten teachers in Riyadh was used. Results: Results revealed (1) a moderate degree of availability of administrative and leadership requirements for inclusion of children with disabilities in the kindergarten stage; (2) higher ranking of items indicating school administrations’ awareness of dissemination of an inclusive culture than those indicating their efforts to provide the material and human resources necessary for the inclusion processes; (3) teachers’ specialization was not statistically significant but years of experience was significant in comprehending administrative efforts. Conclusion: the study provided a clear vision of the administrative and leadership requirements for the inclusion of children with disabilities in the kindergarten stage from their teachers' point of view and the variables that may affect the degree of availability of these requirements.